EDUCATION AS A FACTOR OF ECONOMIC DEVELOPMENT (Pedagogy of Higher and Secondary Education, 2011)
The problems of education as a factor in economic development of society at the pesent stage. The role of knowledge in information-econimic interaction and their influence on the country's competitiveness as an example of the Czech Respublic. Highlighted the role of educational programs in shaping the knowledge economy.
Keywords: education; information society; economic development; knowledge economy